Analisis Strategi Bisnis UMKM Jambi â€œWonderfulplan.Jasadekorâ€ dengan Metode Business Model Canvas (BMC) - Jamira, Anaseputri; Asmas, Denny (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to answer the problem of how to describe the Business Model and Business Strategy Analysis of UMKM Jambi "Wonderfulplan.JasaDekor" using the Business Model Canvas (BMC) Method. This is thought to be an effort to avoid stagnant UMKM growth. The decoration services business sector was chosen as one of the current business trends, in addition to the coffee business trend which was previously discussed in previous research. Qualitative research, with a descriptive approach and case studies is used to answer problems. The policy design and strategic steps that can be provided to optimize the management performance of "Wonderfulplan.JasaDekor" are a combination of improving the performance of Key Partners (KP) and Customer Relationships (CR), which will create a new Value Proposition (VP) and optimize the Value Proposition (VP) previously, thus providing better Revenue Streams (RS) and being able to fulfill appropriate Cost Structures (CsS), as well as providing more optimal profit margins.